Economie socială, capital social şi dezvoltare locală - Neguț, Adriana (Calitatea Vieții, 2013)
In recent years, the interest for social economy has increased, both in terms of theoretical approaches and policy initiatives. The concerns regarding the contribution of social economy and social capital to local economic development have widened as well. The discourse on the role of social economy has expanded: along with its role in generating employment and providing goods and services, it is now recognized its ability to build and strengthen capacities and social capital, in its efforts to meet social integration needs. Due to their flexible nature and the orientation towards social purposes, rather than maximizing profit, the social economy organizations can easily adapt to development needs, taking into account the values of the actors involved in the process. The concept of social capital is being used more frequently by the World Bank, OECD and other organizations in the context of local economic development and social economy, and in recent European policies. This article explores the concept of social capital and the manner in which it is generated and used within the social economy. It presents the perspectives of Bourdieu, Coleman and Putnam on social capital, the distinction between bridging and bonding social capital, and its role in the development process. Reviewing the main risks associated with development policies focused exclusively on social capital – excessive strengthening of bonding social capital and weakening of bridging social capital, and, therefore, the risk of community isolation, increasing latent inequalities or ignoring some forms of social capital, such as trust –, the article does not overrates its role. Trust is one of the elements due to which social enterprise was included in the category of social capital generators, along with its emphasis on cooperation, reciprocity and voluntary activities. Social capital stock has proved an important factor in determining the potential of establishing a social enterprise or developing the community, but is not the only factor to be taken into account, nor it has the ability to substitute other resources. Also, we should not neglect the relationship between bridging and bonding social capital, the excessive tilt of this balance towards one or the other having significant effects on the implementation of local development projects and on the development of social enterprises. On the other hand, the focus on a particular type of social capital in relation to social economy may differ, depending on the stage of development of the social enterprise. Most research on social economy in Romania focused on issues such as the characteristics of social economy organizations, their history and the challenges they have to face, the legislative issues and forms of support. The role of social capital in developing social economy, as part of local economic development, it is not among the areas of interest of recent research projects at national level. Romania is rather poor, both in terms of bridging social capital and in terms of understanding the concept of social economy. Understanding the relationship between social capital and social economy can have important influences for decision makers in order to design policies to strengthen the social economy, a goal for which they were granted substantial funding. A first step in this direction would be to incorporate this dimension in research projects, acknowledging, however, that the impact of social capital is a qualitative one.